2012
DOI: 10.1128/jb.01478-12
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Four Axenic Mycoplasma genitalium Strains Isolated from Denmark, Japan, and Australia

Abstract: The DNA genome of Mycoplasma genitalium currently represents the smallest of all known human bacterial pathogens. Despite their clinical importance in sexually transmitted infection and relevance as model bacterial pathogens, genomic diversity among M. genitalium strains worldwide is unknown. Herein we present the complete draft genome sequences of four geographically diverse strains of M. genitalium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Phylogenetic analysis was performed using the isolates read data (this study) and the published [ 22 ] genomes of samples M2321, M6280, M6320 and M2288 (accession numbers [GenBank: CP003770–3], respectively). Fastq data was generated from published genomes by simulating short-read data in silico .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analysis was performed using the isolates read data (this study) and the published [ 22 ] genomes of samples M2321, M6280, M6320 and M2288 (accession numbers [GenBank: CP003770–3], respectively). Fastq data was generated from published genomes by simulating short-read data in silico .…”
Section: Methodsmentioning
confidence: 99%
“…Despite their importance to human health, there are only 5 fully sequenced M. genitalium genomes to date, largely because of the fastidious nature and slow growth of the organism. They include the recent draft genomes of four M. genitalium strains isolated from patients in Denmark, Japan, and Australia [ 22 ], which were obtained from axenic cultures raised from single colonies and took up to a year to grow from a swab or urine specimens; a procedure normally involving 2 to 15 passages in Vero cells [ 23 , 24 ]. To increase our understanding of the population framework and diversity of M. genitalium we sequenced a set of 21 geographically and temporally diverse M. genitalium strains (1 of them with three isolates from the same patient) as well as other 5 strains available from the ATCC.…”
Section: Introductionmentioning
confidence: 99%
“…These comprised four plant glycolytic parasite species ( Candidatus Phytoplasma asteris [53], Candidatus Phytoplasma austrailense [54], Candidatus Phytoplasma mali [55], Candidatus Phytoplasma solani [56], Candidatus Phytoplasma strawberry [57]), five animal glycolytic parasite species ( Mycoplasma conjunctivae [58], Mycoplasma genitalium [59], Mycoplasma haemocanis [60], Mycoplasma hyopneumoniae [61], Mycoplasma parvum [62]) and seven parasite species known to obtain energy from catabolism of amino acids or amino sugars ( Mycoplasma arthritidis [63], Mycoplasma capricolum [PRJNA16208], Mycoplasma fermentans [64], Mycoplasma hominis [23], Mycoplasma penetrans [65], Mycoplasma putrefaciens [66], Mycoplasma synoviae [67]). A further four parasite species were used for testing the predictive capacity of the model for synonymous codon use ( Mycoplasma crocodyli [68], Mycoplasma hyorhinis [69], Mycoplasma leachii [70], Mycoplasma mycoides [70]).…”
Section: Methodsmentioning
confidence: 99%
“…However, the short read length and high data volume from NGS technologies create problems for assembling highly repetitive sequences (44). In our genome sequencing studies of M. genitalium (45) and Pneumocystis (L. Ma et al, unpublished data; also http://www.broadinstitute .org/annotation/genome/Pneumocystis_group.2/MultiHome .html), we found that it is impossible to assemble highly repetitive sequences (Ͼ1.5 kb) using short reads generated by the 454 and Illumina platforms. One potential alternative approach is the newly developed PacBio SMRT sequencing technology, which is able to generate sequence reads longer than 3 kb (46).…”
Section: Figmentioning
confidence: 99%